2006
DOI: 10.4278/0890-1171-20.5.334
|View full text |Cite
|
Sign up to set email alerts
|

Status of U.S. Military Retirees and Their Spouses toward Achieving Healthy People 2010 Objectives

Abstract: Health-promotion interventions are needed to improve the health status of this population and to achieve the goals set forth in Healthy People 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Both obesity and aging decrease insulin sensitivity, impair the immune response, increase inflammation, weaken the gut-bloodstream barrier, and decrease physical mobility [ 2 ]. Promotion of dietary intervention, exercise, and lifestyle modification, including second-line obesity treatments, to sustain weight loss has been elusive [ 3 , 4 ]. Even though a direct relationship between calorie restriction and health span has been observed in animal models [ 5 , 6 ], controlling food intake in humans is difficult, mainly transient, and often unsustainable because it involves multiple factors including psychological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Both obesity and aging decrease insulin sensitivity, impair the immune response, increase inflammation, weaken the gut-bloodstream barrier, and decrease physical mobility [ 2 ]. Promotion of dietary intervention, exercise, and lifestyle modification, including second-line obesity treatments, to sustain weight loss has been elusive [ 3 , 4 ]. Even though a direct relationship between calorie restriction and health span has been observed in animal models [ 5 , 6 ], controlling food intake in humans is difficult, mainly transient, and often unsustainable because it involves multiple factors including psychological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Diet intervention, exercise, and lifestyle modification have been promoted by the National Institutes of Health (NIH), the United States Department of Agriculture (USDA), and other government institutions, but sustainable weight loss has been elusive. In an intensive diet and behaviour modification program with meal replacements, adults lost 22.6–25.5+1% of their body weight temporarily, but maintained only a 5% weight loss after 3 years (Kress, Hartzell, Peterson, Williams, & Fagan, 2006; Wadden & Frey, 1997). …”
Section: Introductionmentioning
confidence: 99%
“…In a 2006 study, self-reported service members’ health behaviors met or exceeded 7 of the 19 HP2010 objectives assessed, including those related to obesity and exercise [19]. Kress and colleagues assessed HP2010 objectives among military retirees and their spouses and found that fewer retirees and beneficiaries met obesity, exercise, substance use, and healthy eating objectives than national target percentages [20]. Being male, having less than a college degree, and less-than-excellent self-reported health status were associated with a lower likelihood of meeting the objectives [20, 21].…”
Section: Introductionmentioning
confidence: 99%